Murine Typhus, Reunion, France, 2011–2013 - Balleydier, Elsa (Emerg Infect Dis, 2015)
Murine typhus case was initially identified in Reunion, France, in 2012 in a tourist. Our investigation confirmed 8 autochthonous cases that occurred during January 2011–January 2013 in Reunion. Murine typhus should be considered in local patients and in travelers returning from Reunion who have fevers of unknown origin.